Assessment of basic infrastructure in anganwadi centres under integrated child development services scheme in district Amritsar of Punjab - Gill, Kanwal Preet K.; Devgun, Priyanka; Mahajan, S. L.; Kaur, Harpreet; Kaur, Amanpreet (International Journal Of Community Medicine And Public Health, 2017)
Background:In India, Integrated Child Development Services (ICDS) Scheme was launched on 2nd October, 1975. The aim was to provide pre-school non-formal education on one hand and breaking the vicious cycle of malnutrition, morbidity and mortality among mothers and children on the other hand. An anganwadi is the focal point for the delivery of services to the community. Hence, the current study was planned to assess the basic infrastructure in AWCs of Punjab. Methods:A total of 400 anganwadi workers (AWWs), 200 each from rural and urban areas were randomly selected for the study. A pre-designed, pre-tested proforma was administered to selected AWWs. The purpose of the study was explained to them. The data was compiled and analysed by using SPSS 20.0 version. Results:It was observed that out of 400 anganwadis, only 24% of anganwadis had their own allotted building. Only 42% anganwadis had functional Salter weighing machine with them. Weighing machine for adults and children in working condition was available in only 38.2% anganwadis. Nearly half of the anganwadis (50.8%) do not have electricity connection. Water supply was found to be available in 53% anganwadis only. 77.5% anganwadis got regular supply of ration. But utensils for distributing ration were present with only 65.2% anganwadis and 69.3% anganwadis had helper to assist anganwadi worker. Conclusions:Adequate infrastructure along with regular supply of ration need to be ensured for proper functioning of anganwadis.